2020
DOI: 10.1007/s10526-020-10048-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Acanthoscelides obtectus and Zabrotes subfasciatus in stored dried beans

Abstract: This study assesses the feasibility of using natural enemies for the control of Acanthoscelides obtectus Say and Zabrotes subfasciatus Boheman (Coleoptera: Chrysomelidae), key pests of stored dried beans, Phaseolus vulgaris L. (Fabales: Fabaceae). The predatory mites Blattisocius tarsalis Berlese (Acari: Ascidae) and Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) were able to prey on A. obtectus eggs, reducing the bruchid population by more than 60% under both controlled and warehouse conditions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…We observed that Pteromalidae (represented by individuals from the genus Lyrcus ) and Eulophidae (represented by individuals from the genus Horismenus ) were the most abundant families of parasitoids emerging from the bruchine A. schrankiae . Other studies have also identified Pteromalidae (Sharratt and Olckers 2012; Hizal and Parlak 2013; Tuller et al 2015; Sasakawa et al 2016; Morales-Silva et al 2018; Iturralde-García et al 2020) and Eulophidae parasitoids (Gumovsky and Ramadan 2011; Pikart et al 2011, 2015; Tuller et al 2015; Wood et al 2017; Morales-Silva et al 2018, 2019; Hansson et al 2019) attacking bruchines. To the best of our knowledge, this is the first record of Horismenus missouriensis (Eulophidae) and Eupelmus pulchriceps (Eupelmidae) using A. schrankiae as a host.…”
Section: Discussionmentioning
confidence: 96%
“…We observed that Pteromalidae (represented by individuals from the genus Lyrcus ) and Eulophidae (represented by individuals from the genus Horismenus ) were the most abundant families of parasitoids emerging from the bruchine A. schrankiae . Other studies have also identified Pteromalidae (Sharratt and Olckers 2012; Hizal and Parlak 2013; Tuller et al 2015; Sasakawa et al 2016; Morales-Silva et al 2018; Iturralde-García et al 2020) and Eulophidae parasitoids (Gumovsky and Ramadan 2011; Pikart et al 2011, 2015; Tuller et al 2015; Wood et al 2017; Morales-Silva et al 2018, 2019; Hansson et al 2019) attacking bruchines. To the best of our knowledge, this is the first record of Horismenus missouriensis (Eulophidae) and Eupelmus pulchriceps (Eupelmidae) using A. schrankiae as a host.…”
Section: Discussionmentioning
confidence: 96%
“…Populations of Z. subfasciatus, Callosobruchus maculatus, and S. zeamais were reared in 0.8 L glass containers at 28 ± 2 °C, 75 ± 5% relative humidity, and 24 h scotophase. 10,17 Common beans and cowpea beans were used as the food substrate for Z. subfasciatus and C. maculatus, respectively, while popcorn kernels and corn grains were fed to S. zeamais.…”
Section: Percentage Of Surviving Insectsmentioning
confidence: 99%
“…7 Physical methods include moisture content reduction (drying), temperature control (aeration/cooling), grain cleaning, adequate packaging, and application of inert powders. [7][8][9] Biological control employs living organisms, such as Amblyseius swirskii (Ath.-Henr) (Acari, Gamasida, Phytoseiidae), for controlling eggs of Zabrotes subfasciatus (Bohemann, 1833) (Coleoptera: Chrysomelidae), 10 the larval parasitoids Anisopteromalus calandrae (Howard) (Hymenoptera: Pteromalidae) and Lariophagus distinguishandus (Föster, 1841) (Hymenoptera: Pteromalidae), against Callosobruchus chinensis (Linnaeus, 1758) (Coleoptera: Chrysomelidae), 11 and nematodes like Heterorhabditis bacteriophora (Poinar, 1976) (Rhabditida: Heterorhabditidae) and Steinernema feltiae (Filipjev, 1934) (Rhabditida: Steinernematidae), against Sitophilus zeamais (Motschulsky, 1885) (Coleoptera: Curculionidae). 12 Chemical control comprises the application of pesticides, and it can be preventive (with contact insecticides) or curative (phosphine fumigation, for example).…”
Section: Introductionmentioning
confidence: 99%
“…However, environmental pollution and threats to human health due to insecticide residues as well as the risk of pest resistance evolution ( Guedes et al, 2017 ; Dar et al, 2020 ) forced searching for alternative management tools (reviewed in Mohapatra et al, 2015 ; Daglish et al, 2018 ; Rajendran, 2020 ). For example, recent studies on A. obtectus have evaluated efficacy of hermetic storage ( Freitas et al, 2016 ), inert dusts ( Floros et al, 2018 ; Lazarević et al, 2018 ; Prasantha et al, 2019 ), predators and parasitoids ( Iturralde-García et al, 2020 ), insecticidal products of entomopatogenic bacteria and fungi ( Rodríguez-González et al, 2018 , 2020 ), as well as plant-derived products ( Kısa et al, 2018 ; Jevremović et al, 2019 ; Hategekimana and Erler, 2020 ; Lazarević et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%